Expression of CD203c on basophils as a marker of immunoglobulin E-mediated l-asparaginase allergy. Issue 1 (January 2014) - Hino, Moeko; Shimojo, Naoki; Ochiai, Hidemasa; Inoue, Yuzaburo; Ando, Kumiko; Chikaraishi, Koji; Ota, Setsuo; Okimoto, Yuri; Sunami, Shosuke; Nakamura, Ryosuke; Teshima, Reiko; Sato, Yasunori; et al.
Abstract Immediate allergy to l-asparaginase (ASP) is a major obstacle in treating lymphoid malignancies. ASP-specific immunoglobulin G (ASP-IgG) has been used as a surrogate marker. Recently, the CD203c-basophil activation test (BAT) was found to be useful in diagnosing IgE-mediated allergies. We compared the diagnostic utility of the CD203c-BAT to that of ASP-IgG levels in determining ASP allergies in children. Eight ASP allergic reactions occurred over 75 ASP treatment courses. The sensitivity, specificity and area under the receiver operating characteristic curve of CD203c-BAT were similar to the ASP-IgG levels (0.75 vs. 0.85, 0.82 vs. 0.78 and 0.81 vs. 0.85, respectively). Positive skin prick test results in patients with ASP allergy suggested that ASP-IgE was one of the key players in ASP allergy. A combination of the BAT with the ASP-IgG level had the highest specificity (0.95) and positive predictive value (0.62), which permitted us to identify ASP allergy more effectively.